O contributo de Cruz de Carvalho para a história do design em Portugal - Coelho, Diogo João Rocha dos Santos, 1974- (2014)
José Maria Cruz de Carvalho is one of the Portuguese Design History's name. We look deep into the life and work of this selfmade designer once a painter. His name has been referred several times, but until today, his work, had not been analysed as a whole. As we travel through his professional life, we take notice of his chosen paths and life's chances. Cruz de Carvalho's career is long and fruitful, working as a painter, decorator, sketcher, arquitect, teacher, foreman and woodworker, however, it was as a designer that he stood out and became notable. Inside the field of design he got mixed with, mostly interior design, furniture design and exhibition design, and in someway with design management, graphic design and design filosofy as well teaching. Cruz de Carvalho is the creator of the Altamira furniture brand, in 1957, designing new facilities, stores, serial models and general conception of the brand's product public presentations, putting in practice, for the first time in Portugal, a corporate design integrated policy. In 1967, creates the Interforma brand, establishing with success new production and design filosofies, in Portugal and abroad. In another aspect, throughout his carrer, designs and manages the assembly of exhibitions at the Museu Nacional de Arte Antiga, Museu Nacional do Traje, Palácio Nacional da Ajuda, Paço Ducal de Vila Viçosa, and others. Cruz de Carvalho, together with João Constantino, laid the foundation for the 1st Portuguese Design Exhibition, in 1971. With a relevant, pioneer and awarded work in the national scene, the designer is a member of the APD, ICOM and APOM, and contemporary of Daciano da Costa, António Garcia, Nuno Portas, Eduardo Afonso Dias, Hélder Batista and Conceição Silva. Through the study and careful analysis of his trajectory, we intend to bring more solid data to the making of the Portuguese Design History and contribute for the enrichment of the Portuguese Design Identity. In the basis of this study, is an investigation of a vast set of original documents of the designer's personal collection that allows us to access his project thinking and to the way he practiced his design profession since the fifties